Clinically Classified Periodontitis and Its Association in Patients with Preexisting Coronary Heart Disease. (19th June 2013) - Chrysanthakopoulos, Nikolaos A.; Chrysanthakopoulos, Panagiotis A.
Abstract : The aim of this retrospective study was to investigate possible associations between clinically classified periodontitis as determined by assessing its severity and diagnosed coronary heart disease in outpatients referred to a specialist clinic for neurosurgery treatment. A total of 2, 912 individuals were clinically examined for periodontal disease experience by using probing pocket depth (PPD) and clinical attachment loss (CAL). Socioeconomic, oral health behaviour, and general health related information was collected by using a self-administered questionnaire. Statistical analysis of the questionnaire items was performed by using multivariate logistic regression analysis model. The results showed that the occurrence of hypertension (OR = 2.42, 95% CI = 1.52–3.84), smoking (OR = 1.97, 95% CI = 1.25–3.11), classified periodontitis (OR = 1.79, 95% CI = 1.15–2.77), and the high level of serum C-reactive protein (OR = 1.74, 95% CI = 1.05–2.89) were significantly associated with the presence of coronary heart disease. These observations strengthen the role of some of the traditional causative risk factors for coronary heart disease while a significant association was recorded between diagnosed coronary heart disease and clinically classified periodontitis which is considered as a risk factor for coronary heart disease.